2020
DOI: 10.1007/s11768-020-0048-8
|View full text |Cite
|
Sign up to set email alerts
|

A review on charging behavior of electric vehicles: data, model, and control

Abstract: The adoption and usage of electric vehicles (EVs) have emerged recently due to the increasing concerns on the greenhouse gas issues and energy revolution. As a part of the smart grid, EVs can provide valuable ancillary services beyond consumers of electricity. However, EVs are gradually considered as nonnegligible loads due to their increasing penetration, which may result in negative effects such as voltage deviations, lines saturation, and power losses. Relationship and interaction among EVs, charging statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…Detailed review of related datasets and optimization methods can be found in Ref. [18]. Among these works, the idea of EV Aggregators (EVAs) is an effective way to schedule EVs fleet which can save computation and communication burden [19] .…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed review of related datasets and optimization methods can be found in Ref. [18]. Among these works, the idea of EV Aggregators (EVAs) is an effective way to schedule EVs fleet which can save computation and communication burden [19] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…An event e is defined as a set of state transitions that have certain common properties [20] and EBO is mathematically equivalent to the partially observable MDP [21] . Generally, the event space is much smaller compared with the original MDP and many works applied EBO to address the EV charging problem [18,22] . Note that these works have not explored the fact that some events only capture local state changes, while some events capture global state changes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many control schemes have been proposed to overcome the negative impacts of EV charging. A control strategy using data-driven models has been implemented to relax power system components and prevent excessive loading due to EV charging demand [27][28][29]. Demand side management (DSM) works to guarantee EVs' demand satisfaction in all grid situations and certifies grid stability [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to meet the following criteria: Provide power to other on-board equipment and subsystems, e.g., lights, cabin heating, ventilation and air conditioning (HVAC) systems, radio, power drives, electronic control units, etc. [4,5,18].…”
mentioning
confidence: 99%